Quantum Learning-Based Arabic Language Learning Innovation for Generation Z - Lina Ulfa Fitriani, (Edumaspul: Jurnal Pendidikan, 2026)
Advances in science and technology have brought significant changes to the world of education. Quantum Learning presents itself as a learning approach capable of creating a more enjoyable, communicative, effective, and relevant learning environment for Generation Z (Gen Z) students, who are synonymous with digital technology. This approach emphasizes emotional engagement, experience, and real-world contexts to help students grasp material more quickly and meaningfully. Learning Arabic, which was often considered difficult and boring due to the dominant use of traditional methods, has become more innovative with the use of digital media in Arabic learning. This paper was conducted using literature analysis from various journals, books, and relevant sources. The results of the study indicate that the Quantum Learning approach can be used as a reference in practicing the four Arabic language skills (maharah lughowiyah al-arba'ah) for Gen Z students, increasing their motivation to learn Arabic because this approach refers to interactive learning and the integration of students' personal experiences. This Quantum Learning model is considered relevant for implementation as an innovation in Arabic language learning for students, especially Generation Z today. Abstrak Perkembangan ilmu pengetahuan dan teknologi membawa perubahan signifikan dalam dunia pendidikan. Quantum Learning hadir sebagai pendekatan pembelajaran yang mampu menciptakan suasana belajar lebih menyenangkan, komunikatif, evektif dan relevan bagi peserta didik generasi Z (gen Z) yang identik dengan teknologi digital. Pendekatan ini menekankan keterlibatan emosi, pengalaman dan konteks nyata untuk membantu peserta didik memahami materi secara lebih cepat dan bermakna. Pembelajaran Bahasa Arab yang tadinya sering dianggap sulit dan membosankan karena dominan menggunakan metode tradisional oleh peserta didik menjadi lebih berinovasi dengan pemanfaatan media digital dalam pembelajaran Bahasa Arab. Penulisan ini dilakukan dengan metode analisis literatur dari berbagai jurnal, buku dan sumber yang relevan. Hasil kajian menunjukkan bahwa model pendekatan dalam quantum learning dapat dijadikan acuan dalam mempraktikkan ketrampilan berbahasa Arab yang empat (maharah lughowiyah al-arba’ah) bagi peserta didik gen Z menjadikan mereka lebih termotivasi dalam mempelajari Bahasa Arab sebab pendekatan ini mengacu pada pembelajaran interaktif dan integrasi pengalaman personal peserta didik. Model quantum learning ini dinilai relevan diterapkan sebagai inovasi pembelajaran Bahasa Arab pada peserta didik khususnya generasi Z saat ini.